2019
DOI: 10.1111/1744-7917.12724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mummy consumption on fitness and oviposition site selection on Harmonia axyridis

Abstract: Intraguild predation (IGP) has been commonly reported between predators and parasitoids used as biological control agents as predators consuming parasitoids within their hosts. However, the effect of parasitoid–mummy consumption on the fitness of the predator and subsequent oviposition site selection have not been well studied. In our study, we conducted two laboratory experiments to examine the influence of Aphidius gifuensis Ashmead (Hymenoptera: Braconidae) mummies as prey on fitness and subsequently ovipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…Development times for each stage and total immature stage of A. aphidimyza that fed on parasitized M. persicae were longer than those of predator larvae feeding on unparasitized M. persicae. Our results are consistent with studies of C. septempunctata, H. convergens, H. axyridis, and P. japonica that subsisted on mummified aphids, demonstrating that predators could slow their ontogenetic development [7,10,34]. Our study using A. aphidimyza revealed that its longevity, oviposition period, and fecundity were all significantly affected by its feeding on parasitized aphids.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Development times for each stage and total immature stage of A. aphidimyza that fed on parasitized M. persicae were longer than those of predator larvae feeding on unparasitized M. persicae. Our results are consistent with studies of C. septempunctata, H. convergens, H. axyridis, and P. japonica that subsisted on mummified aphids, demonstrating that predators could slow their ontogenetic development [7,10,34]. Our study using A. aphidimyza revealed that its longevity, oviposition period, and fecundity were all significantly affected by its feeding on parasitized aphids.…”
Section: Discussionsupporting
confidence: 91%
“…Consumption of parasitized aphids and mummies could adversely affect the development, body size, survival, and behavior of aphid predators [6,7,10,34,35]. Our results showed that consumption of parasitized aphids did not influence the survival rates of immature A. aphidimyza individuals, but it did significantly delay their overall developmental time and also reduced the predator's longevity, fecundity and predation rates.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This study also demonstrated that overall aphid mummies were a low-quality diet and longer developmental time was observed on mummified aphid diet. Yu et al (2020) reported that the larval developmental time of H. axyridis was significantly prolonged when fed with mummified prey.…”
Section: Biological Parametersmentioning
confidence: 99%